The Research Trends of Rice Husk-Based Briquettes Using Bibliometric Analysis - Adam Nugraha; Siti Fatimah; Asep Bayu Dani Nandiyanto (Penerbitan Universitas Trisakti, 2022)
As the huge consumption of rice worldwide, the amount of production waste also increases. The purpose of this study was to investigate rice husk utilization for briquettes solid fuel which has aroused a great concern in the last few decades and growing number of related publications. Therefore, a bibliometric analysis of these publications may provide a direction of novel topics and prospective research trends. The related global literatures published between 2012 and 2021 have been scanned from ScienceDirect collection database. “Biochar briquettes” and “rice husk briquettes” are used as the keywords. VOSviewer is applied to perform the bibliometric analysis of these articles. In the same time, literature review has been done to analyze the research trends on rice husk-based briquetting. Totally 400 publications on the topic of biochar briquettes were identified and “biomass” with a total link strength of 90 appeared as the most frequent keywords.